Effect of cholera toxin on vaccine-induced immunity and infection in murine schistosomiasis mansoni. - Akhiani, A A (1993)
Intradermal vaccination of mice with soluble adult worm antigen (SWAP) in combination with Mycobacterium bovis BCG (Swedish strain) induced significant protection against subsequent infection with Schistosoma mansoni cercariae. When cholera toxin (CT) was used as an adjuvant in combination with SWAP or fraction A, no significant protection was observed. However, intradermal vaccination in combination with CT triggered a strong anti-SWAP antibody response and induced a strong delayed-type hypersensitivity response to schistosome antigens (SWAP or fraction A), one significantly higher than that in the SWAP-BCG group. In addition, vaccinating mice intranasally with SWAP or cercarial antigen together with CT as adjuvant failed to induce any significant protection. Surprisingly, mice given CT alone intranasally revealed a significantly enhanced worm burden. These findings suggest that mucosal application of CT may modulate the host-parasite relationship in favor of parasite survival.